A Framework for Calculating Time-Efficient Diffusion MRI Protocols for Anisotropic IVIM and An Application in the Placenta - Slator, Paddy J.; Hutter, Jana; Ianus, Andrada; Panagiotaki, Eleftheria; Rutherford, Mary A.; Hajnal, Joseph; Alexander, Daniel C. (Mathematics and Visualization, 2019)
We develop a framework for calculating clinically-viable diffusion MRI (dMRI) protocols for anisotropic IVIM modelling. The proposed multi-stage framework combines previous approaches to dMRI protocol optimisation: first optimising b-values by minimizing Cramer-Rao lower bounds on parameter variances, and subsequently optimising gradient directions jointly to provide maximum angular coverage across all shells. This removes unnecessary measurements of closely spaced b-values with the same gradient directions, which encode very similar information, and hence reduces the total number of dMRI measurements. We applied the framework to establish an organ-specific, data-driven, set of optimised b-values and gradient directions for dMRI of the placenta. The optimised protocol leads to higher contrast-to-noise ratios in parameter maps compared to a naive protocol of comparable scan time. Applying this framework in other organs has the potential to reduce scanning times required for anisotropic IVIM modelling.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Anisotropic IVIM; Cramer-Rao lower bound; Diffusion MRI; Experimental design; IVIM; Microstructural modelling; Placenta